Population Transcriptomics Reveals Gene Flow and Introgression Between Two Non-sister Alpine Gentians - Chen, Chunlin; Yang, Wenjie; Liu, Jianquan; Xi, Zhenxiang; Zhang, Lei; Hu, Quanjun (Frontiers in Ecology and Evolution, 2021)
Distributional shifts driven by Quaternary climatic oscillations have been suggested to cause interspecific hybridization and introgression. In this study, we aimed to test this hypothesis by using population transcriptomes and coalescent modelling of two alpine none-sister gentians. Previous studies suggested that historical hybridizations occurred between Gentiana siphonantha and G. straminea in the high-altitude Qinghai-Tibet Plateau although both species are not sister to each other with the recent divergence. In the present study, we sequenced transcriptomes of 33 individuals from multiple populations of G. siphonantha and G. straminea. The two species are well delimited by nuclear genomic SNPs while phylogenetic analyses of plastomes clustered one G. straminea individual into the G. siphonantha group. Further population structure analyses of the nuclear SNPs suggested that two populations of G. siphonantha were admixed with around 15% ancestry from G. straminea. These analyses suggested obvious genetic introgressions from G. straminea to G. siphonantha. In addition, our coalescent-based modeling results revealed that gene flow between two species continued since Last Glacier Maximum, which might have leaded to the observed introgressions. Our results underscore the significance of transcriptome population data in determining timescale of interspecific gene flow and direction of the resulting introgression.